ANALISIS KELAYAKAN FINANSIAL UNIT USAHA MESIN PEMANEN PADI (COMBINE HARVESTER) DI KECAMATAN SEPUTIH RAMAN KABUPATEN LAMPUNG TENGAH - Hari Murti; Wan Abbas Zakaria; Dyah Aring Hepiana Lestari (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2017)
This research aims to analyze financial feasibility of rice harvesting machine (combine harvester) business unit and its sensitivity. Location was selected purposive in the Seputih Raman Subdistrict, Central Lampung Regency. Respondents were all ten owners of the rice harvestinsg machine (combine harvester) with three differences in investment in machinery, namely in 2013, 2014, and 2015. Data were analyzed by quantitatively using measurement criteria of financial viability and sensitivity analyzes. The results showed that: business unit of rice harvesting machine (combine harvester) is financially viable as indicated by  NPV values of Rp779,027,757.73 in 2013, Rp638,765,707.48 in 2014, and  Rp417,306,800.57 in 2015; IRR 77.40 percent (2013), 70.55 cpercent (2014), and 67.29 percent (2015); Gross B/C of 1.39 (2013), 1.35 (2014), and 1.30 (2015); Net B/C of 3.35 (2013), 2.99 (2014), and 2.92 (2015); PP of 2.18 (2013), 2.24 (2014) and 2.33 (2015) from the economic life of the machine for seven years, and business unit of rice harvesting machine (combine harvester) is still viable despite the drop in harvest area of 4.77 percent, a decrease in rental machine rate of 5 percent, and an increase in operating cost of 6.51 percent.Key words: combine harvester, financial, sensitivity